Risky Sexual Behaviour among HIV-Infected Adults in Sub-Saharan Africa: A Systematic Review and Meta-Analysis. (14th April 2023) - Wondmeneh, Temesgen Gebeyehu; Wondmeneh, Ruhama Gebeyehu
Abstract : Background . Risky sexual behaviour raises serious public health concerns. The pooled prevalence of risky sexual behaviours among adults living with HIV/AIDS in sub-Saharan Africa was unknown. This systematic review determined the pooled prevalence of risky sexual behaviours and associated factors among HIV-infected adults in sub-Saharan Africa. Methods . International databases such as PubMed, CINAHL, Google Scholar, and African Journals OnLine were systematically searched to identify articles. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline was used to conduct the review. All necessary data were extracted independently. Heterogeneity and publication bias were assessed by I -squared statistics and Egger's test, respectively. The random-effects meta-analysis model was used to estimate the pooled prevalence. The association between predictors and dependent variable was determined by a pooled odds ratio (OR) with a 95% confidence interval (CI). Result . In this study, 3713 articles were retrieved from various databases, and 22 of them were included. The pooled prevalence of risky sexual behaviour in sub-Saharan Africa was 36.16% (95% CI: 28.36-44.34) with significant heterogeneity among studies (I 2 = 98.86 %, p < 0.001 ). Risky sexual behaviour was significantly associated with the nondisclosure of HIV status (AOR = 1.97, 95% CI: 1.18, 2.76) and alcohol consumption (AOR = 2.29, 95% CI: 1.21, 3.36). Conclusion . A significant percentage of participants engaged in risky sexual behaviour. Risky sexual behaviour was associated with failure to disclose HIV status and alcohol consumption. Healthcare professionals should advise HIV-positive patients on risk reduction measures like disclosing their HIV status to their sexual partners and avoiding alcohol use in order to promote consistent condom use. PROSPERO Protocol Registration . The protocol for this systematic review and meta-analysis has been registered (record ID: CRD42020170967, 09/06/2022).